PENINGKATAN KOMPETENSI GURU MADRASAH DALAM BIDANG PENULISAN KARYA TULIS ILMIAH UNTUK MENDUKUNG GERAKAN AYO MEMBANGUN MADRASAH (GERAMM) - Akhmad Sruji Bahtiar; Abdul Wafi (JPM PAMBUDI, 2019)
The movement let's build a madrasa (GERAMM) is a madrasa innovation program to improve quality towards a great and dignified madrasa. Among the GERAMM programs, one of them is the Madrasah Literacy Movement (GELEM) program with the aim of generating literacy activities in madrasah with the main target of teachers, principals, supervisors and students. The problem in this service is how to improve the quality of teachers in the field of writing scientific papers especially writing (a) research proposals, (b) reports of research results, and (c) scientific publications. The method used in this service is a workshop in which it is conducted with lectures, discussions and questions and answers. The results of the workshop were able to improve the ability of teachers in the field of scientific papers by 31% from the initial value before the workshop. The contribution of this service is to realize literacy programs in madrasas by equipping teachers with scientific writing skills, the GERAMM program is able to boost madrasa innovation towards superior madrasas.